A Systematic Review and Meta-analysis of Sex Differences in Morbidity and Mortality of Acute Lower Respiratory Tract Infections Among African Children - Adebola E. Orimadegun; Adedayo A. Adepoju; Landon Myer (Mazandaran University of Medical Sciences, 2020)
Context: Although biological sex influences Acute Lower Respiratory Tract Infections (ALRIs) morbidity and mortality patterns in children living in sub-Saharan Africa, the exact mechanism about the effect is unknown.  Objective: We assessed the quality and strength of evidence on the association of sex with incidence, etiology, and outcomes of ALRI in African children. Data Sources, Study Selection, and Data Extraction: We systematically searched electronic databases for publications from 1971-2016 in PubMed, African Journals Online, and Google scholar for ALRI literature in the African children. We used (pneumonia OR bronchiolitis OR "community-acquired pneumonia" OR CAP OR "hospital-acquired pneumonia" OR "nosocomial pneumonia" OR "ventilator-acquired pneumonia" OR "lung abscess" OR "pleural effusion" OR "empyema thoracis") AND (sex OR gender) AND (Africa OR Sub-Saharan) as search terms. We included the published peer-reviewed journal articles reporting on incidence, etiology, and case fatality. We summarized the findings using narrative and meta-analysis methods. Results: We included 14 studies with sex-related data; the median (IQR) number of reported pneumonia cases was 148 (87-770) and 114 (56-599) for male and female patients, respectively. Only two studies reported a sex-specific incidence. The odds of sex were in favor of male sex, and the chances of identification of Respiratory Syncytia Virus (RSV) were significantly lower in males than in females (OR=0.60; 95% CI: 0.42, 0.86). Estimates from 9 studies showed that the death rate for males was significantly higher than for females (OR=1.26; 95% CI=1.20-1.33). Conclusions: Sex-disaggregated data on incidence, etiology, and case fatality of pneumonia are scarcely reported in studies published in Africa. However, males appear to die more often than females, and females more likely to have RSV infection.